METHODS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE - Гиязов Дониер Эркинович (Web of Journals Publishing, 2025)
This article discusses topical issues of methods of teaching Russian as a foreign language (RFL) in modern conditions. The need for transition from the traditional grammatical-translation method to communicative, activity and interactive approaches is emphasized. Modern pedagogical technologies, digital tools and features of the formation of intercultural competence in foreign students are analyzed. The article presents the results of the pedagogical experiment, proving the effectiveness of the proposed integrative approach.
Keywords: Russian as a foreign language, teaching methods, communicative approach, digital technologies, intercultural communication, motivation, language competence, Russian as a foreign language.